Personality and Cognition: Sociability Negatively Predicts Shoal Size Discrimination Performance in Guppies - Lucon-Xiccato, Tyrone; Dadda, Marco (Frontiers in Psychology, 2017)
Evidence from a growing number of organisms suggests that individuals show consistent performance differences in cognitive tasks. According to empirical and theoretical studies, these cognitive differences might be at least partially related to personality. We tested this hypothesis in the guppy, Poecilia reticulata, by comparing individuals with different degree of sociability in the discrimination of shoals formed by a different number of conspecifics. We found that individual guppies show repeatability of sociability as expected for personality traits. Furthermore, individuals with higher sociability showed poorer shoal size discrimination performance and were less efficient in choosing the larger shoal compared to individuals with low sociability. As choosing the larger shoal is an important strategy of defense against predators for guppies, we discuss this relationship between personality and cognition in the light of its fitness consequences.